Vacuum-assisted breast biopsy after neoadjuvant systemic treatment for reliable exclusion of residual cancer in breast cancer patients - Kölbel, Vivian; Pfob, André; Schäfgen, Benedikt; Sinn, Peter; Feißt, Manuel; Golatta, Michael; Gomez, Christina; Stieber, Anne; Bach, Paul; Rauch, Geraldine; Heil, Jörg (Annals of surgical oncology, 2022)
About 40 % of women with breast cancer achieve a pathologic complete response in the breast after neoadjuvant systemic treatment (NST). To identify these women, vacuum-assisted biopsy (VAB) was evaluated to facilitate risk-adaptive surgery. In confirmatory trials, the rates of missed residual cancer [false-negative rates (FNRs)] were unacceptably high (> 10%). This analysis aimed to improve the ability of VAB to exclude residual cancer in the breast reliably by identifying key characteristics of false-negative cases.